Comparison of measured rain attenuation in the 10.982-GHz band with predictions and sensitivity analysis - Abdulrahman, Yusuf A; Rahman, Tharek A; Islam, Md Rafiqul; Olufeagba, Benjamin J; Chebil, Jalel (John Wiley & Sons, Ltd, 2014)
The campaign to collect rain attenuation data on terrestrial links had commenced in Malaysian tropical climates for almost two decades. The terrestrial data so far collected have been greatly utilized to derive useful statistics for various microwave applications, such as frequency scaling, rain rate conversion factor, 1-min rain rate contour maps, wet antenna losses, and fade slope duration analysis. However, there is still severe scarcity of rain attenuation data on earth–space links in Malaysia. The results of the 2-year measurement (January 2009–December 2010) of rain rates and rain-induced attenuation in vertically polarized signals propagating at 10.982 GHz have been presented in this paper. The rain attenuation over the link path was measured at Islamic International University Malaysia and compared with ITU-R P.618-10 and Crane global models in this paper. The test results show that the two prediction models seem inadequate for predicting rain attenuation in the Ku-band in Malaysia. Sensitivity analysis performed on measured data also reveals that the sensitivity variables depend on rain rate.